Effects of Biochar With Inorganic and Organic Fertilizers on Agronomic Traits and Nutrient Absorption of Soybean and Fertility and Microbes in Purple Soil - Liu, Ming; Linna, Cholidah; Ma, Shumin; Ma, Qun; Guo, Jinge; Wang, Fenfen; Wang, Longchang (Frontiers in Plant Science, 2022)
Background: Soybean (Glycine max L.) plays a vital role since it is not only a source of food and energy for people but also a source of high protein feed supplement for livestock. Biochar is one kind of organic matter that can be added into soil as a soil amendment to improve its quality. Aims:The objectives of our study were to evaluate the effects of biochar, inorganic and organic fertilizer application on plant growth, chlorophyll content, photosynthesis gas exchange, and yield of soybean as well as fertility and microbial community in purple soil, and to appraise the possible reduction rate of inorganic fertilizer under the biochar application. Methods: A pot experiment was conducted with three levels of biochar, two levels of inorganic fertilizer and two levels of organic fertilizer in a randomized complete block. Results: The results indicated that the low rate of biochar together with half rate of inorganic fertilizer and organic fertilizer increased plant growth of soybean. Meanwhile, biochar alone increased chlorophyll contents, root growth and yield of soybean. The photosynthesis gas exchange of soybean was increased by the high rate of biochar with half rate of inorganic fertilizer and organic fertilizer. Furthermore, the low rate of biochar with half or full rate of inorganic fertilizer and organic fertilizer increased N, P, and K uptake of soybean. Soil nutrient contents and soil microbial community were increased by the high rate of biochar with half rate of inorganic fertilizer and organic fertilizer. Conclusions: In conclusion, application of biochar can reduce the use of organic and inorganic fertilizers, improve the agronomic traits and yield of soybean, and play a positive role in soil nutrients and soil microorganisms.